Structure and Photoluminescence of the Ordered Vacancy Compound Cu3In7Se12 - Salomo Salomo; Yanuar Yanuar (Institut Teknologi Bandung, 2003)
We have synthesized polycrystalline Cu3In7Se12 bulk crystals by the horizontal Bridgman method. The crystal structure of the ordered vacancy compound is investigated by X-ray diffraction and Rietveld refinement analysis. The lattice parameters are a = 5.7616 Å and c = 11.5391 Å and the space group is uniquely specified to be I42m. The photoluminescence spectra are investigated at the liquid helium temperature range in order to determine the defect level of this compound. Photoluminescence spectra of the sample exhibit two transitions at 1.08 eV and 0.95 eV which are identified as donor-acceptor transitions.